A Simple Automation of a Peircean Decision Procedure. - White, Richard B. (Transactions of the Charles S. Peirce Society)
The article describes a simple decision procedure for the graphical sentential logic of philosopher C. S. Pierce, the system of alpha graphs. The decision procedure is then implemented by a LISP program CSProve. The article also offers examples of CSProve as it ran on a desktop computer and indicates how the program is easily adapted to parallel processing.